Analisis Kualitas Pelayanan Bus Samsat Keliling Unit Pelayanan Pendapatan Daerah Medan Selatan Badan Pengelolaan Pajak Dan Retribusi Daerah Provinsi Sumatera Utara - Hubalillah Hubalillah; Badaruddin Badaruddin; Heri Kusmanto (PERSPEKTIF, 2022)
The purpose of this article is to analyze the service and the inhibiting factors of the Samsat Bus service around the Regional Revenue Service Unit (UPPD) of South Medan BPPRDSU. This study uses a descriptive method with qualitative analysis techniques. With data collection techniques from interviews, documentation, and observation. Based on the results of interviews and observations using 4 indicators from Tjiptono (2002) regarding the service quality of the Mobile Samsat Bus at Simpang Pemda Medan Selayang District, it is good or quality. However, comfort is still not good or inadequate because the facilities are still limited. Barriers that are often found are people who complain about the facilities. This is because the existing facilities are still unsatisfactory. Then the undisciplined officers of the Mobile Samsat Bus at the Simpang Pemda Medan Selayang District. Namely, the Samsat Bus Officers at the Simpang Simpang Pemda Medan Selayang Subdistrict enter and leave the office on time. And the community wants the operation time of the Samsat Roving Bus at the Medan Selayang District Government to be extended.